Hubungan Antara Perilaku Masyarakat Terhadap Sanitasi Lingkungan Dengan Kejadian Demam Berdarah Dengue (Dbd) Di Wilayah Sungai Lulut Banjarmasin - Noraisyah, Dila; Melviani, Melviani; Rahmadani, Rahmadani (Innovative: Journal Of Social Science Research, 2024)
Human behavior and the environment are two factors that continue to interact, poor community behavior, environmental conditions that do not meet health requirements are risk factors for transmitting dengue fever. The aim of the research is to determine the relationship between individual factors, environmental factors, 4M plus environmental sanitation, waste management and the incidence of dengue fever. This research method includes observational descriptive quantitative analytic with a cross sectional approach. The results show that age and gender have no relationship with the incidence of dengue fever with a p-value of 1.000 and 0.404. Occupation and education have no relationship with the incidence of dengue fever with p-values ​​of 0.209 and 0.209. The implementation of 4M plus environmental sanitation and waste management is related to the incidence of dengue fever with a p-value of 0.000 and 0.003, where the significance value is stated to be >0.05. Conclusion There is no relationship between individual behavioral factors and environmental factors and the incidence of dengue fever. However, there is a relationship between the implementation of 4M plus and waste management.